2017
DOI: 10.18632/oncotarget.16115
|View full text |Cite
|
Sign up to set email alerts
|

Stat3-positive tumor cells contribute to vessels neoformation in primary central nervous system lymphoma

Abstract: With the aim of elucidating the relationship between Stat3 expression and tumor vessels abnormalities in the PCNLs, in this study we evaluated Stat3 and pStat3 expression by Real-time PCR and by immunohistochemistry in biopsy sections from PCNSL patients. Correlations of the expression levels with the presence of aberrant vessels were analyzed by confocal laser microscopy analysis, using FVIII as endothelial cell marker, CD133 and nestin as cancer stem cell (CSC) marker, CD20 as tumor cell marker, and Stat3. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…These data confirm also our previously published data showing that, in primary central nervous system lymphoma, tumor vessels appeared lined by endothelial cells expressing both FVIII and STAT3 signals, while in the control brain tissue, only FVIII-positive vessels were detectable [18]. Endothelial cells lining these vessels are heterogeneous, expressing FVIII and STAT3, and presumably, originally they are vascular progenitor cells.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm also our previously published data showing that, in primary central nervous system lymphoma, tumor vessels appeared lined by endothelial cells expressing both FVIII and STAT3 signals, while in the control brain tissue, only FVIII-positive vessels were detectable [18]. Endothelial cells lining these vessels are heterogeneous, expressing FVIII and STAT3, and presumably, originally they are vascular progenitor cells.…”
Section: Discussionsupporting
confidence: 91%
“… 53 55 One study showed that even Nestin, a specific marker of neural stem cells, can be used to identify CSCs. 56 These markers can be utilized not only to identify and isolate CSCs but also to predict treatment efficacy in the clinic, shedding light on how CSCs contribute to poor survival and tumor progression. 55 The markers shared between CSCs and normal stem cells imply that there are some similar biological characteristics between them, such as self-renewal and endless proliferation, under the suitable conditions.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“…Studies have reported an association between angiogenesis and prognosis in PCNSL [ 16 , 17 ]. However, the effects of baseline characteristics, genomic profiles, and treatment modalities on overall survival and outcomes of PCNSL have not been studied.…”
Section: Introductionmentioning
confidence: 99%